The Challenge of National Regulation Reform in Facing Legal Technology Disruption - Khuan, Hendri (PT. Anagata Sembagi Education, 2025)
The development of digital technology has brought significant disruption in the national legal system, giving rise to normative and institutional challenges that have not been fully anticipated by existing regulations. Innovations such as artificial intelligence (AI), blockchain-based smart contracts, and electronic court systems (e-courts) have structurally changed the way the law works, but at the same time have raised new issues related to legality, accountability, and procedural justice. Law Number 19 of 2016 as an amendment to the ITE Law and Law No. 27 of 2022 concerning Personal Data Protection has not been responsive enough in dealing with the ever-growing complexity of digital law. In addition to legal vacancies, multiple interpretations of norms, and regulatory fragmentation, the Indonesian legal system also faces limitations in harmonization with international legal standards such as GDPR, as well as low institutional capacity in implementation. Through a normative juridical approach with the analysis of primary and secondary legal materials, this study highlights the importance of legal reform based on regulatory foresight, legal harmonization, and institutional transformation. Digital legal reform in Indonesia must be anticipatory, adaptive, and interdisciplinary, in order to be able to ensure legal certainty, human rights protection, and the rule of law in the midst of increasingly intensive and disruptive digital globalization